Shadow ILL Services: How Scholarly Pirate Websites and Hacking Affect ILL. Issue 5 (20th October 2019) - Kehnemuyi, Kaitlin; Larsen, Sylvie C.
Abstract: Full-text research pirating sites are a fact of life at this point. Regardless of how we personally feel about this issue, the fact that students, researchers, and patrons are turning away from the library as a legitimate source for research documents means libraries' numbers are affected. We are all seeing usage numbers go down, it's a trend throughout ILL. This could be for a number of reasons: use of OA and pre-print servers, better collection development, or an increase in use of pirating or black market PDF websites. Regardless, this decrease in numbers can lead to a decrease in funding for our departments. At the same time we have seen cases of abuse in institutional logins. During this discussion we will look at some examples of attempted phishing and impersonation techniques used by "pirates, " our library patrons' motivations for using these sites, consequences for the user as well as the institution, and the role of ILL in this conundrum.